PROFESSIONAL MOBILITY IN THE CONTEXT OF PREPARATION OF FUTURE PEDAGOGUES TO PROFESSIONAL SELF-DEVELOPMENT - Valentyna A. Frytsiuk; Iryna G. Gerasymova (Alfred Nobel University Publisher, 2019)
The article considers professional mobility of future pedagogues and professional self-development of students. It highlights the main features of a future teacher as a subject of professional self-development. The subjective approach with respect to the problem of self-development of personality was revealed. In this case, both teacher and student discuss problems together. The teacher uses a democratic style of communication. The article states that students can form their own self-development which affects the social maturity of an individual. «The readiness of prospective teacher for continuous professional self-development» is considered as the student's ability for purposeful reflexive activities, which is associated with the design and implementation of quality changes in personality's identity and practical realization of subjective experience in the field of professional self-determination and self-realization on the basis of conscious self-regulation of one's own educational and professional activities. It is proved that the use of the authors' scientific and methodological system of prospective teacher's training for continuous professional self-development helps in personal and professional growth of prospective teachers, their comprehension of necessity of purposeful continuous professional self-development; integrative and theoretical training, increasing level of obtained professionally directed knowledge; practical operating training, formation of practical skills and abilities for professional self-development; combination of individual and psychological qualities, which are important for continuous professional self-development and prospective professional activities in general; orientation at self-analysis and self-esteem of one's own professional self-development. The article summarizes scientific views of the concept of «professional mobility». Professional mo- professional mobility». Professional mo- ». Professional mo- . Professional mobility is considered from the sociological, psychological and pedagogical approaches. According to sociology, mobility implies a change in the position of a person in the social structure of society. Mobility implies changes in activities. Professional mobility of future teachers is considered as internal readiness for qualitative changes and as an ability for acquiring new professional knowledge. The necessity of preparation of students for professional mobility is proved. It will ensure the efficiency and competitiveness of teachers in future professional activities.